The zoomorphic forms in traditional keris hilts. - Ibrahim, Fawazul Khair (Faculty of Built Environment, UTM, 2004)
In traditional keris hilts, there are several types of images representing the handle. The zoomorphic forms are one of them, which used several animals as the keris hilts. This article looks into three major animals, namely, horse, elephant and insect. It is discovered that these three types of animals have gone through three major evolutions. The article will discuss each type, particularly on the form, the origin, the materials used and the surface treatment decorating the form.